2009
DOI: 10.4161/psb.4.12.9943
|View full text |Cite
|
Sign up to set email alerts
|

The role of receptor interactions in regulating ethylene signal transduction

Abstract: The phytohormone ethylene is perceived in Arabidopsis by a five-member receptor family. Earlier work has demonstrated that the basic functional unit for an ethylene receptor is a disulfide-linked homodimer. We recently reported in The Journal of Biological Chemistry that the ethylene-receptor ETR1 physically associates with other ethylene receptors through higher order interactions, suggesting the existence of receptor clusters. Here we consider the implications of such clusters upon the mechanism of ethylene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 20 publications
2
16
0
Order By: Relevance
“…The analysis of gain-of-function mutants etr1-1 and etr1-3 (Bleecker et al, 1988;Chang et al, 1993) has shown that ETR1 mediates ethylene-triggered stomatal closure in Arabidopsis (Desikan et al, 2006). However, several current models have revealed that this kind of mutation may affect signal output from the other receptors (Grefen et al, 2008;Gao and Schaller, 2009;Liu and Wen, 2012). Cho et al (2012) also showed that the dominant gain-of-function mutant etr1-1 contains a recessive mutation in ACCUMU-LATION AND REPLICATION3 (ARC3).…”
Section: Resultsmentioning
confidence: 99%
“…The analysis of gain-of-function mutants etr1-1 and etr1-3 (Bleecker et al, 1988;Chang et al, 1993) has shown that ETR1 mediates ethylene-triggered stomatal closure in Arabidopsis (Desikan et al, 2006). However, several current models have revealed that this kind of mutation may affect signal output from the other receptors (Grefen et al, 2008;Gao and Schaller, 2009;Liu and Wen, 2012). Cho et al (2012) also showed that the dominant gain-of-function mutant etr1-1 contains a recessive mutation in ACCUMU-LATION AND REPLICATION3 (ARC3).…”
Section: Resultsmentioning
confidence: 99%
“…Bacterial two-component receptors are modeled to form higher order clusters through direct interactions with adjacent receptors, where the signaling state of one receptor affects the signaling state of surrounding receptors (Bray et al, 1998;Duke and Bray, 1999;Shimizu et al, 2003). Similar models have been invoked for ethylene receptors (Binder and Bleecker, 2003;Binder et al, 2004aBinder et al, , 2004bGao et al, 2008;Grefen et al, 2008;Gao and Schaller, 2009;Liu and Wen, 2012). The crystal structure of the ETR1 receiver domain has been determined, revealing a homodimer that is stabilized by the C terminus, which forms an extended b sheet (Müller-Dieckmann et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the signal output of full-length ethylene receptors may be cooperatively mediated to the ETR1 N terminus via a CTR1-indpendent pathway ( Fig. 5A; Gamble et al, 2002;Xie et al, 2006;Gao et al, 2008;Gao and Schaller, 2009;Chen et al, 2010;Liu and Wen, 2012). Given that excess CTR1 7-560 prevents ethylene receptor signaling (Huang et al, 2003), if the constitutive ethyleneresponse phenotype of CTR1-Nox is suppressed by expression of the ETR1 N terminus, ETR1 N-terminal signaling may not be mediated via full-length ethylene receptors.…”
Section: -349mentioning
confidence: 99%
“…Therefore, etr1-1 1-349 predominantly cooperates with subfamily I receptors to mediate the ethylene receptor signal output (Xie et al, 2006). Biochemical and transformation studies showing that ethylene receptors can form heterodimers and that each receptor is a component of high-molecular-mass complexes explain how ethylene receptors may act cooperatively (Gao et al, 2008;Gao and Schaller, 2009;Chen et al, 2010).…”
mentioning
confidence: 99%